Comparative Analysis of Joint Life Endowment Insurance Premium Reserves: Zillmer Method Versus Prospective Method and The Impact of Zillmer Level - Hafnani, Hafnani; Maulidi, Ikhsan; Nurmaulidar, Nurmaulidar; Alindo, Sesda; Apriliani, Vina (Syiah Kuala University, 2025)
The insurance company collects premium reserves obtained from the difference between the value of benefits and the value of premium payments at a time of coverage. One method of premium reserve is prospective reserve, where the calculation is based on the difference between the present value of the benefits to be received and the present value of the net premiums that will come in accordance with a predetermined annuity. This research aims to determine the amount of premium and premium reserves in joint life endowment insurance using the Zillmer method which uses the concept of prospective reserves with gross premiums as the basis for calculations. Then we compare the result with premium reserves using prospective methods, and see the effect of the Zillmer level variable on the amount of premium reserves. The results of this study can be concluded that the value of joint life joint insurance premiums increases according to age when starting insurance and the reserves of joint life insurance premiums always increase every year, until at the end of the insurance coverage premium reserves will reach the same value as the amount of compensation. The value of the premium reserve is influenced by the value of the Zillmer level used; the greater the Zillmer level value, the greater the profit earned by the life insurance company.